Study of Production Methods of Polyethylene Fittings - Ro‘ziboyevich, Cho‘liyev Jamshid; o‘g‘li, Yuldoshev Javohir Abdijalil (International Journal on Orange Technologies, 2023)
Pipe and pipe fittings of organic polymeric material such as polyethylene have become widely known and used for diverse purposes such as for conveying fluids. Piping systems of polyethylene material have been found to be desirable especially in view of the ease with which such systems may be fabricated. The paper is a market study that aims to identify the problems encountered in welding polyethylene pipe - fittings assemblies. The market study is made within companies that activate in the field, gathering answers from polyethylene certified welders, technicians responsible with welding techniques, and from those who supervise and manage these activities.